The Effect of Diabetes Mellitus Foot Exercises on the Stability of Blood Sugar Levels in Patients with Diabetes Mellitus: A Literature Review - Putri Intan Miladiana; Fahrun Nur Rosyid (Indonesian Journal of Global Health Research, 2024)
Diabetes is a degenerative disease that has special characteristics, namely hyperglycemia due to abnormal insulin secretion and suboptimal insulin performance or both. Treatment measures taken by health/medical personnel include: pharmacological treatments such as administering drugs and non-pharmacological treatments such as routine metabolic control, vascular control, ulcer evaluation, foot care and other exercise measures such as foot exercises. Objective: of this study was to apply diabetic foot exercise therapy to reduce blood sugar levels in patients with diabetes mellitus Method: uses a literature review method through a data search base through search engines such as PubMed, Croseff and Google Scholar, with keywords namely: "Foot Exercise" OR "Foot Gymnastics" AND "Blood Sugar Level" AND "DM" OR "Diabetes Mellitus" AND "Sugar Level" with a time span of 2020 - 2024. The search results obtained a total of 9 articles that were eligible for review according to the PRISMA flowchart. The inclusion criteria used are adult patients aged 30-60 years who experience diabetes mellitus, using Quasy Experiment, RCT and Narrative methods and articles in English that are freely accessible and Indonesian language journals. The intervention was diabetic foot exercise therapy, and aerobic exercise therapy and exercise media using newspapers. Results: showed that the therapy effectively helped reduce blood sugar levels in patients with diabetes mellitus. Conclusions: effectively helped reduce blood sugar levels.